Analisis Bibliometrik terhadap Kemampuan Berpikir Kritis Matematika Berdasarkan Pemecahan Masalah Berbasis VOS Viewer Bibliometric - Wulandari, Riska; Zulfah, Zulfah; Astuti, Astuti (Lembaga Penelitian dan Pengabdian Masyarakat, 2023)
The purpose of this bibliometric analysis to see opportunities and developments in research trends related to critical thinking mathematics ability based on VOS Viewer-based problem solving. The method used is bibliometrics by collecting article data from 2015-2021 through the Google Scholar site with Publish or Perish software for 1,000 journals. The results showed that the most publications in 2015 were 265. Variables related to critical thinking mathematics ability that have opportunities and novelties to be researched in the future are the flipped classroom, high order thinking skills and math anxiety variables.